PENGARUH PELIMPAHAN WEWENANG, ALOKASI ANGGARAN DAN KEPEMIMPINAN TERHADAP KINERJA KECAMATAN DI KABUPATEN GARUT - Jujun Juhana; Sadu Wasistiono; Irwan Tahir; Kusworo (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This study discusses the influence of delegation of authority, budget allocation and leadership to the performance of sub-districts in Garut Regency, West Java Province, Indonesia. The study uses a quantitative approach by taking a sample of 286 respondents from a population of 1003 people. Data collection in this study using questionnaires. Data analysis techniques using SEM analysis. The magnitude of the influence of delegation of authority on sub-district performance reached 0.754 determined by the political will of the district head to delegate part of government authority to the sub-district head, the political will of the district head to make the sub-district the center of community service, regional technical institutions' delegation to delegate part of the technical authority that can be carried out by the district head, budget support and personnel to exercise delegated authority. The magnitude of the effect of budget allocations on a sub-district performance that reaches 0.651 is determined by comprehensive and disciplined, flexibility, predictability, honesty, information, transparency, and accountability. The amount of leadership influence on a sub-district performance that reaches 0.655 is determined by the guidance and direction given by the sub-district head, the behavior of the sub-district head's relationship with the sub-district apparatus, and the level of readiness of the sub-district apparatus.